Effects of Zingiber officinale Aqueous Extract on Semen Characteristic and Some Blood Plasma, Semen Plasma Parameters in the Broilers Breeder Male - Saeid, J.M.; Shanoon, A.K.; Marbut, M.M. (International Journal of Poultry Science, 2011)
To investigate the effects of Zingiber Officinale on male reproductive functions and study the mechanisms underlying these effects, aqueous extract of Zingiber officinale were administered in drinking water to two groups of male broilers breeder (24wk age) at 5% and 10%. A third group served as control and received the treatment vehicle, distilled water. Treatment lasted for 28, 32, 36, 40 and 44 wk age. Ejaculate volume, sperm concentration, counts, movements, motility and abnormality, semen plasma cholesterol, protein and glucose, the antioxidant malonhydialdehyde, glutathione and blood serum LH, FSH and testosterone, were determined. The treatment caused a significant increase (p<0.05) in the weight of the testis and There were dose and duration dependent increases in ejaculate volume, sperm concentration, counts, movements and a significant decrease (p<0.05) in motility and abnormality. There was also a significant increase (p<0.05) in semen plasma cholesterol, glucose and a significant decrease (p<0.05) in protein. Antioxidant malonhydialdehyde were significantly reduced (p<0.05), glutathione and blood serum LH, FSH and testosterone serum level were significantly increase (p<0.05). Our results indicated that extract of Zingiber officinale possesses pro-fertility properties in male broiler which might be a product of both its potent antioxidant properties and androgenic activities.